Fracture development and controlling factors at metamorphic buried-hill reservoirs of Bozhong 19-6 gas field in Bohai Bay, East China - Mi, Lijun; Fan, Tingen; Fan, Hongjun; Niu, Tao; Gong, Lei; Su, Xiaocen; Sun, Yonghe; Cheng, Yuqi (Frontiers in Earth Science, 2023)
Fractures of multi-scales and multi-origins are primary storage space and effective seepage channels for metamorphic buried-hill reservoirs. They not only allow communication between various pores to enhance storage and seepage capacity, but also are essential for high yields. Fracture development and controlling factors at metamorphic buried-hill reservoirs of Bozhong 19-6 Gas Field were investigated based on imaging log, core data, experiments, e.g., thin sections and scanning electron microscope, and outcrop description. Results show that structural fractures, weathering fractures and dissolution fractures were developed in the metamorphic buried-hill reservoirs in the study area, among which structural fractures and weathering fractures are the most popular ones. However, fracture types varied obviously among different structure positions. Lithology, fault, weathering crust and ancient landform are primary factors affecting fracture distribution. Fractures were prone to be developed at lithology with high bright mineral contents. Faults were characterized by a dual structure including fault core and damage zone. Fracture density followed a decreasing trend with increasing distance from faults. Damage zone could be identified when fracture density was consistent with regional fracture density. The width of the damage zone was determined by factors such as fault scale and structure location. Well-connected weathering fractures were popular at the leached unit, with structural fractures of secondary importance. The unweathered unit was dominated by structural fractures with low density.